Muslims and mosques in France: navigating the ‘cultural/religious’ dichotomy through God’s witnessing and the holism of Islam - El-Yousfi, Amin (Religion, state & society, 2021)
The French state’s laïcité is characterised by a paradox of neutrality: the state claims neutrality while constantly intervening in the religious field, including in the definition of religion in relationship to categories like culture. How do Muslims navigate this paradoxical secular governmentality in relation to the legal and social representation of mosques’ activities as either religious or cultural? Muslims have been able to register new mosques in France either as ‘cultural’ (based on the 1901 law of associations) or ‘religious’ (based on the 1905 law of separation) associations. However, in recent years (particularly after the 2015 Paris terrorist attacks) state representatives have pushed local mosque leaders to adopt the ‘religious’ status. This contribution not only discusses the secular nature of the cultural/religious dichotomy and its role in the process of establishing mosques in France since the 1926 creation of the Grand Mosque of Paris, but also analyses how Muslim pieties centred around God’s witnessing (shāhidiyya) and the holism (jamʿiya) of Islam encounter and operate through a central component of the French secular governmentality of mosques, the cultural/religious distinction.